Thyroid dysfunction in patients of depression and anxiety and response to therapy - ., Harsha; ., Amandeep; Jeenger, Jitendra; Ahlawat, R. S.; Subberwal, Manju (International Journal of Research in Medical Sciences, 2021)
Background: Depression and anxiety are the most common psychiatric presentation in thyroid dysfunction. Aim of the study was to determine the thyroid profile in patients with depressive and anxiety symptoms and to determine the change in symptoms with correction of thyroid profile. Methods: This longitudinal observational study was conducted in patients presented with depressive or anxiety symptoms who visited the psychiatry out patient department (OPD) first time. Two groups were made based on the serum thyroid profile. First group, (n=27) was patients with depression and anxiety with hypothyroidism (experimental group) and second was (n=123) without hypothyroidism (control group). Experimental group, (n=27) was then exposed to thyroxine, 15 patients came for first follow up and 11 patients came for second follow up. Results: The 63% of patients in the experimental group and 62.6% of patients in the control group were of female gender, 66.7% and 33.3% of patients in the experimental group had depressive disorder and anxiety disorder respectively. TSH level of 11 patients of experimental group had significantly less value in first follow up compared to entry point (p=0.002). Generalized anxiety disorder (GAD) 7 scores were significantly lower in first and second follow up than that of the entry point in 11 patients of experimental group (p=0.008, 0.016 respectively). Conclusions: Many patients of the clinical diagnosis of depression (17.6%) and clinical diagnosis of anxiety (18.75%) had hypothyroidism during the first visit to the psychiatry OPD. There was significant reduction in the hypothyroid patients of the serum thyroid stimulating hormone (TSH) value and anxiety scores during the follow up after treatment with levothyroxine.